Autonomous Land Vehicles Steps towards Service Robots - Berns, Karsten; Puttkamer, Ewald (Vieweg+Teubner Verlag : Imprint: Vieweg+Teubner Verlag, 2009)
The economic potential of autonomous mobile robots will increase tremendously during the next years. Service robots such as cleaning machines and inspection or assistance robots will bring us great support in our daily lives. This textbook provides an introduction to the methods of controlling these robotic systems. Starting from mobile robot kinematics, the reader receives a systematic overview of the basic problems as well as methods and algorithms used for solving them. Localisation, object recognition, map building, navigation and control architectures for autonomous vehicles will be discussed in detail. A survey of specific service robot applications is also included. This book is a useful introduction to mobile robotics for beginners as well as advanced students and engineers. Content Historical overview of autonomous land vehicles - Vehicle kinematics - Sensor systems - Where am I?: The localisation problem - Map building - Navigation strategies - Control architectures - Software frameworks Target Groups - Students from the fields of computer science, mechanical engineering and electrical engineering, specializing in autonomous mobile systems - Engineers with a special interest in the development of service robots About the Authors Prof. Dr. Karsten Berns and Prof. Dr. Ewald von Puttkamer are experts in the field of mobile robots. They are lecturers for embedded systems and robotics at the TU Kaiserslautern. Especially in the area of mobile robots, focusing on wheel-driven and biologically inspired robots, they have taught several courses.